Non-gold ohmic contact for GaN-on-Si HEMT - Zhuang, Yihao (Nanyang Technological University, 2023)
High power high frequency HEMT transistors are transistors that run at high frequency (100 kHz and above) for high-speed switching and high-power delivering applications. Kinds of III-V semiconductor materials have been studied to be applied to HEMT like GaAs, InP, and GaN. Owing to the high breakdown voltage and high saturation velocity, GaN is an ideal material that is capable of developing high-power and high-frequency HEMT. Due to the superior characteristics, GaN HEMT has been widely applied in power electronics and RF power amplifiers. The current mature state-of-art GaN HEMT is based on small size GaN on SiC (usually up to 6”), using the conventional Au-based III–V device manufacturing process, whose cost is high and cannot be decreased. In addition, due to the high diffusivity of gold, the possible pollution makes it impossible to transfer to CMOS compatible process. Recently, with the development of advance epitaxial growth technology, the growth of GaN layers on a large-diameter Si substrate becomes practicable. Compared with conventional Au-based III–V device manufacturing process using SiC as the substrate, a new CMOS-compatible Gold free process using Si substrate will not only allow higher-volume lower-cost fabrication but also provides the opportunity for on-chip integrated GaN HEMTs. This project aims to develop a CMOS-compatible Au-free ohmic contact for GaN-on-Si HEMT which could achieve comparable performance to the conventional Au-based GaN HEMTs. Few Au-free metal stacks have been studied and realized on the chip for characterization. In the end, a new metal stack with a low contact resistance and smoother surface compared with the Au-based Ti/Al/Ni/Au stack has been achieved. The GaN HEMTs using the metal stack are also produced and tested.